Efektivitas Implementasi Strategi True Or False Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Fiqih Di Kelas Vii Madrasah Tsanawiyah Nurur Rahmah Sentol Pademawu Pamekasan - Zakiyatur Rahmah; Nahlah Nahlah; Zaitun Zaitun; Lailatul Qomariyah; Moh Syamsul Arifin (Institut Kariman Wirayudha Sumenep, 2023)
The Effectiveness of Implementing the True or False strategy in increasing students' interest in learning fiqh in class VII of Madrasah Tsanawiyah Nurur Rahmah Sentol Pademawu Pamekasan, To determine the effectiveness of the Implementation of the True or False strategy and also to determine the increase in students' interest in learning fiqh. There are two main problems in this study, 1) How is the effectiveness of the Implementation of the True or False strategy in increasing students' interest in learning fiqh in class VII of Madrasah Tsanawiyah Nurur Rahmah Sentol Pademawu Pamekasan? 2) What are the supporting and inhibiting factors of the Implementation of the True or False strategy in increasing students' interest in learning fiqh in class VII of Madrasah Tsanawiyah Nurur Rahmah Sentol Pademawu Pamekasan? The research method used in this study is a qualitative descriptive approach in which the results of the research obtained are in the form of descriptive data, the data sources of this study are the principal, Fiqh subject teachers, and also students. The data analysis was carried out using a qualitative descriptive method by reducing data, presenting data, and verifying the data obtained. The results of the research that the researcher has conducted are found that first, it is very effective, conducive because students can be enthusiastic about following the ongoing learning and students can grow to be positive in learning so that students' interest in learning has begun to increase, second, the supporting factors for the use of the True or False strategy in increasing students' interest in learning in the subject of fiqh at Madrasah Tsanawiyah Nurur Rahmah Sentol Pademawu Pamekasan are adequate media, students who are enthusiastic and enthusiastic in following the subject and the teacher's extensive experience will certainly make it easier for students to receive the subject matter well. With that, students' enthusiasm and interest in learning are getting better and increasing. The inhibiting factors for the use of the True or False strategy in increasing students' interest in learning in the subject of Fiqh in class VII of Madrasah Tsanawiyah Nurur Rahmah Sentol Pademawu Pamekasan are students who still lack confidence and are embarrassed in applying the strategy. In addition, the application of the strategy takes a long time due to the lack of student abilities.